Change of structural and magnetic property due to zinc substitution and sintering temperature of nano-crystalline Cobalt ferrite. (3rd March 2020) - Nasrin, S.; Chowdhury, F.-U.-Z.; Hossen, M. M.; Hoque, S. M.
ABSTRACT: Co1– x Zn x Fe2 O4 ( x  = 0.2, 0.4, 0.6 and 0.8) were synthesized using typical wet chemical co-precipitation technique. The ferrite specimen have been sintered at 700°C and 900°C for three hours in air. X-ray diffraction (XRD) diffractogram and Mössbauer spectroscopy technique were employed to describe the nano-ferrites. The single-phase spinel cubical structure was confirmed from XRD studies. Employing vibrating sample magnetometer (VSM), saturation magnetization, remanent magnetization, etc. have been determined. The value of coercivity confirmed that all the samples were soft ferrites. Ferromagnetic to superparamagnetic transition has been seen by Mössbauer spectroscopy. Complex permeability has been determined using an impedance analyzer. The real and imaginary part of initial permeability along with loss tangent was, and loss tangent was calculated within the frequency range 1 kHz to 120 MHz. It shows the constant value at the high-frequency range that is identical properties for the ferrite samples to apply the materials for storage device applications.